MORAL EDUCATIONAL THINKING MUḤAMMAD ‘ALĪ AL-ṢĀBŪNĪ IN THE TAFSĪR ṢAFWATU AL-TAFĀSĪR - Fithria, Maulida (Sekolah Tinggi Agama Islam Sadra, 2024)
The reality of life in today’s dynamics, we often see delinquency committed by children and adolescents who should reflect good character in themselves, but in their implementation have a bad character in their lives both in the school, community, and family environments. This article discusses the thought of Muḥammad ‘Alī al-Ṣābūnī’s moral education in Tafsīr Ṣafwatu al-Tafāsir which examines various aspects of Qur’anic scholarship. This research uses a library research method, with a descriptive qualitative analysis approach. The result of this research is Muḥammad ‘Alī al- Ṣābūnī actively writing and devoting his knowledge to education, one of his famous works is the book of Tafsīr Ṣafwatu al-Tafāsīr, this book is compiled from the core explanations of great commentaries that are detailed, concise, structured until it becomes clear and straightforward. Moral education is a guide to moral principles and special temperaments, habits that must be owned and made a habit by children from childhood to adulthood. The purpose of moral education is to form humans as supreme and perfect beings who have good behavior and deeds toward fellow humans, fellow creatures, and their Gods to achieve happiness both in this world and in the hereafter. The moral education studied through Tafsīr Ṣafwatu al-Tafāsir includes the nature of honesty, qana‘ah, and obedience. If these qualities can be implemented properly, then the evil that is rife will disappear, a clean heart will always be decorated with good deeds, and vice versa, a dirty heart will always be decorated with bad deeds.